ISOLATED APPENDICULAR TUBERCULOSIS - Waqar, S H; Malik, Zafar I; Zahid, M A (Journal of Ayub Medical College Abbottabad, 2005)
Tuberculosis is still very common in developing and under developed countries. Each year, 3 million people die of this disease world wide. Tuberculosis can affect almost any part of body. The commonest presentation of abdominal tuberculosis is ileo-caecal disease, but isolated appendicular involvement is also rarely seen. Although many cases have been reported from neighbouring countries, a search on national literature has shown no such report from Pakistan. We report a case of appendicular tuberculosis that presented in Accident and Emergency Department of Pakistan Institute of Medical Sciences, Islamabad. Keywords: Abdominal tuberculosis, Appendicitis, Tuberculosis